The effect of optimum, indication-specific imaging fields on the radiation exposure from CBCT examinations of impacted maxillary canines and mandibular third molars - Anne-Mari Ilo; Janna Waltimo-Sirén; Elmira Pakbaznejad Esmaeili; Marja Ekholm; Mika Kortesniemi (Acta Odontologica Scandinavica)
Objective Indication-specific optimum field-of-views (FOVs) have been assessed for CBCTscans of impacted maxillary canines and mandibular third molars, as 40∅ × 35 mm and 35∅ × 35 mm, respectively. The objective was to investigate possible changes in absorbed organs and effective doses, for these two imaging indications, performing CBCTexaminations with optimum FOV sizes instead of commonly used FOVs. Additionally, radiation exposure-induced cancer risk was calculated for both imaging indications with optimum FOVs.